Cross-talk between lipopolysaccharide tolerance and AGEs in the regulation of macrophage inflammation and cholesterol efflux - Santos, Danielle Ribeiro; Mello Santana, Monique de Fatima; Palanca, Eduarda; Vancini, Milena Gomes; de Assis, Sayonara Ivana Santos; Santos, Aritania Sousa; Barbeiro, Denise Frediani; Ariga, Suely Kunimi Kubo; Correa-Giannella, Maria Lucia; Soriano, Francisco Garcia; Passarelli, Marisa (Frontiers in Immunology, 2026)
IntroductionImmune cell infiltration with high expression of receptors for advanced glycation end products (RAGE) and Toll-like receptor 4 (TLR4) promotes vascular inflammation and accelerates atherosclerosis. Advanced glycated albumin (AGE-albumin) primes macrophages for heightened inflammatory responses to lipopolysaccharide (LPS). Here, we investigated whether LPS-induced tolerance modulates AGE-driven inflammatory priming and cholesterol efflux in macrophages.MethodsCholesterol-enriched bone marrow–derived macrophages (BMDMs) and RAW264.7 macrophages were subjected to LPS tolerance induction, treated with control (C)- or AGE-albumin, and rechallenged with LPS. In parallel, LPS tolerance was induced in vivo by repeated low-dose LPS injections, followed by BMDM differentiation, cholesterol loading, albumin treatments, and secondary LPS stimulation. Tumor necrosis factor (TNF) secretion was assessed by ELISA, gene expression by RT-qPCR, and HDL-mediated ¹4C-cholesterol efflux using conditioned media or direct HDL incubation.ResultsIn BMDMs, LPS tolerance reduced TNF secretion following C-albumin treatment but not AGE-albumin. In RAW264.7 macrophages, TNF secretion was reduced by 53% and 77.6% after C- and AGE-albumin treatment, respectively. BMDMs from LPS-tolerant mice exhibited reduced TNF secretion following both albumin treatments. Gene expression analysis revealed that AGE-albumin selectively increased Ager and Tlr4 expression in tolerant BMDMs, whereas C-albumin was associated with broad suppression of pro-inflammatory genes. Conditioned media from tolerant BMDMs markedly enhanced HDL-mediated cholesterol efflux in naïve macrophages, while direct exposure of tolerant BMDMs to AGE-albumin reduced HDL-mediated efflux by 40%.DiscussionThese findings demonstrate that LPS tolerance promotes an atheroprotective macrophage phenotype characterized by attenuated inflammatory signaling and enhanced cholesterol efflux. However, this protective immunometabolic program is selectively disrupted by AGE exposure, highlighting a critical interface through which chronic metabolic stress may override innate immune tolerance and contribute to atherosclerotic progression.